If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(12y+36)/(y-6)=1
We move all terms to the left:
(12y+36)/(y-6)-(1)=0
Domain of the equation: (y-6)!=0We multiply all the terms by the denominator
We move all terms containing y to the left, all other terms to the right
y!=6
y∈R
(12y+36)-1*(y-6)=0
We get rid of parentheses
12y-1*(y-6)+36=0
We move all terms containing y to the left, all other terms to the right
12y-1*(y-6)=-36
| 3y-10=y-38 | | 73-v=220 | | 6(2x-3)-4x=-26 | | 12+1/2(x+5)=2x+22 | | 6(2x-3)-6x=5 | | 289=240-w | | 2x+3(2x-6)=6 | | –3p–10=5 | | x÷6+x+2=x+11-5(4-x) | | 17+20+13w=20w−12 | | 172=58-y | | q2+1=50 | | –18d+8=–17d | | 2x+5=3x× | | n-18=-13 | | x+0.15x=7068 | | 9x+22=33x | | x+0.15x=240 | | M^3-4m-9=0 | | Z^3-4z-9=0 | | 88/4x+12=36/2x | | 5x+7=9x+2 | | 25x+x=100–50= | | 3x^+7x+16=16 | | (3x-1)×4=74 | | x=6x+3=5x−8 | | X+6x+3=5x−8 | | 5y+34=7y+42 | | X7-2=5x+10 | | 4(x+4)=-2x-14 | | 2x-6+9x=5 | | 9m−3m−2=0 |